Analisis Semiotika Film Pertaruhan The Series - M. Ridho Ilahi; Sumaina Duku; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "Semiotic Analysis of The Series Betting Film". The purpose of this research is to find out the meaning of denotation, connotation, and myths in the film "Betting The Series", and to find out the message contained in the film " Betting The Series". The type of research used is descriptive research with a qualitative approach. Data collection techniques used are primary data and secondary data. The object of this research is the film " Betting The Series" which has eight episodes. The data analysis technique used is Rolnd Barthes semiotic analysis. The results of this study are the meanings of denotation, connotation, and myth in the film "Betting The Series". Denotation is the first stage that uses the Rold Barthes semiotic analysis method, connotation is the original nature of signs, and myth is a second level system of meaning. The messages contained in the film "Betting The Series" are hard work, passion, sacrifice, never give up, and be responsible for solving problems.    KEYWORDS: